Digitalization in management accounting and control: an editorial - Klaus Möller; Utz Schäffer; Frank Verbeeten (Journal of Management Control, 2020)
Digitalization has the potential to disrupt the management accounting domain. It may not only affect the digital landscape of the organization and the associated business models, but also management accounting and control practices as well as the role of the controller. This editorial discusses these developments by introducing the concept of digitalization and describing its impact on the field of management accounting and control.
Keywords: 330; Digitalization; Management accounting; Controller roles; Future of finance